High blood pressure in children: clinical and health policy implications - Falkner, Bonita; Lurbe, Empar; Schaefer, Franz (The journal of clinical hypertension, 2010)
J Clin Hypertens (Greenwich). Hypertension is a global problem, affecting both developed and developing nations. In addition to being a major cause of morbidity and mortality, hypertension places a heavy burden on health care systems, families, and society as a whole. Despite evidence of an increasing prevalence of hypertension among youth, the consequences of early onset are poorly established and often overlooked. Childhood hypertension is often asymptomatic and easily missed, even by health professionals. Target organ damage is detectable in children and adolescents, however, and hypertension continues into adulthood. Additional strategies to improve cardiovascular health among children and adolescents are needed, including methods to achieve healthy lifestyles at home and in school, improved systems for diagnosis, and research on mechanisms and timing of interventions. The burden of hypertension in the young will continue to grow unless it is given the attention it deserves by policy makers, health care providers, schools, parents, and society. This report aims to increase awareness of the problem of hypertension in childhood. Recent reports on prevalence and target organ injury are discussed and health policy initiatives to improve blood pressure control are proposed.